PENGARUH BOPO DAN CAR TERHADAP NPF (Studi Kasus Pada Bank Umum Syariah Tahun 2015-2020) - Suteja, Siti Yuningsih (COMPETITIVE, 2023)
The purpose of this study is to determine whether the dependent variable in this study can be influenced by the independent variable. The population in this study were 14 Islamic Commercial Banks with the sampling technique used was purposive sampling. Obtained a sample of 5 Islamic Commercial Banks registered with the OJK. In this study, multiple regression was used to test the hypothesis. Based on the results of the simultaneous test, it is known that NPF can be affected by BOPO and CAR together. Based on the partial test, NPF can be affected by BOPO and NPF can be influenced by CAR.